Specific oligosaccharide form of the Rhizobium meliloti exopolysaccharide promotes nodule invasion in alfalfa. - Battisti, L (1992)
Rhizobium meliloti strain SU47 produces both high molecular weight (HMW) and low molecular weight (LMW) forms of an acidic exopolysaccharide, succinoglycan. Genetic studies have shown that succinoglycan is required for alfalfa root nodule invasion. We found that LMW succinoglycan, when applied exogenously to alfalfa roots, restored nodule invasion to exoA, exoB, exoF, and exoH mutants. Nodule initiation signals were not involved, since LMW succinoglycan from R. meliloti nodD1D2D3 and nodA mutants and from luteolin-induced wild-type cultures elicited effects similar to LMW succinoglycan from the uninduced wild-type strain. In contrast, LMW fractions from an exoA mutant, nonsuccinylated LMW succinoglycan, and HMW succinoglycan did not promote invasion, nor did LMW exopolysaccharides from R. leguminosarum bv. trifolii and Rhizobium sp. strain NGR234. LMW succinoglycan could be separated by anion-exchange chromatography into several distinct subfractions differing in repeating subunit multiplicities (monomer, trimer, and tetramer) and charge. When tested singly, only the most charged, tetrameric form was active. These results show that a specific oligosaccharide form of succinoglycan promotes nodule invasion in alfalfa. The implications for the mode of action of succinoglycan are discussed.